2022
DOI: 10.3389/fpsyg.2022.806784
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Core Disgust and Moral Disgust on Moral Judgment: An Event-Related Potential Study

Abstract: Core disgust is elicited by physical or chemical stimuli, while moral disgust is evoked by abstract violations of moral norms. Although previous studies have pointed out these two types of disgust can affect behavior and spatial dimensions of moral judgment, less is known about how moral and core disgust affect the temporal neural processing of moral judgment. In addition, whether moral and core disgust are only related to purity-based moral judgment or all kinds of moral judgment is still controversial. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 73 publications
(111 reference statements)
0
1
0
Order By: Relevance
“…Second, despite emotions being known to play a crucial role in advertising [79][80][81][82], emotional responses in the context of YouTube in-stream advertising have been little explored, and in particular, no contributions concerning the role of disgust, which is a primary emotional mediator of advertising effects [88][89][90][91], and/or based on the facial expression analysis (FEA) were provided to shed light on the issue addressed by this paper. In this context, the application of facial coding for the investigation of moral disgust during the view of in-stream ads, due to its sensitivity to nonbodily violations (e.g., betrayal or deception) and moralistic anger [102,103], contributed to the emergence of valuable findings, whose interpretations are consistent with the proposed framework [124][125][126][127]. In addition, unlike other measures, disgust-related facial expressions proved to be the most responsive cues to the variation of the non-ad items' presence, as significant differences emerged on all multiple pairwise comparison tests.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, despite emotions being known to play a crucial role in advertising [79][80][81][82], emotional responses in the context of YouTube in-stream advertising have been little explored, and in particular, no contributions concerning the role of disgust, which is a primary emotional mediator of advertising effects [88][89][90][91], and/or based on the facial expression analysis (FEA) were provided to shed light on the issue addressed by this paper. In this context, the application of facial coding for the investigation of moral disgust during the view of in-stream ads, due to its sensitivity to nonbodily violations (e.g., betrayal or deception) and moralistic anger [102,103], contributed to the emergence of valuable findings, whose interpretations are consistent with the proposed framework [124][125][126][127]. In addition, unlike other measures, disgust-related facial expressions proved to be the most responsive cues to the variation of the non-ad items' presence, as significant differences emerged on all multiple pairwise comparison tests.…”
Section: Discussionmentioning
confidence: 99%
“…However, limiting the scope of disgust to its association with food, as a mere foodrelated emotion, is highly inaccurate, as the fundamental role of moral disgust would be ignored. In contrast to core disgust, which occurs in response to physical or chemical stimuli, moral disgust arises in response to abstract violations of moral norms which can be further divided into bodily violations (e.g., sexual taboos) and nonbodily violations (e.g., betrayal or deception) [102,103]. While moral disgust associated with bodily violations has received considerable attention in advertising, in particular by studies focused on controversial advertising [104] which demonstrated its negative effect on ad attitude [105] and even behavior [106], the role of moral disgust associated with nonbodily violations has been far less taken into account in advertising research.…”
Section: Emotions Disgust and In-stream Video Adsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bidirectional representational relationship between moral concepts and physical attributes shows that impurities causing core disgust, such as dirt and stink, can affect behavior and spatial dimensions of moral judgment. For example, research showed that both moral violations involving and not involving impurity promoted the detection of disgusted faces [ 34 ], and moral violations with impurity cues elicited a higher severity of moral judgments than those without impurity cues [ 35 ]. However, this relationship was modulated by the degree of core disgust priming; one study had found that moral severity ratings for moral transgressions after the presentation of neutral images were significantly higher than those after the presentation of highly disgusting images [ 36 ].…”
Section: Introductionmentioning
confidence: 99%